Leading with resident voices: facilitating resident participation toward inclusive, socially sustainable community - Silva, Carron Roxanne, author; Gines, Donna Cooner, advisor; Fothergill, Wendy, advisor; Enns, Kellie, committee member; Frederiksen, Heidi, committee member (Colorado State University. Libraries, 2021)
The word "sustainable" has become a buzzword in environmental, social, and economic development. However, as it relates to "community", it refers more closely to the way citizens organize themselves and create social connections. Furthermore, social sustainability is more closely linked to agency, self-efficacy, social capital, and engagement, with a view to enacting inclusive and equitable social change. The focus of this study was to examine how participants residing in an affordable housing complex define inclusive community, what challenges to creating an inclusive community they experience in their daily life, and what best practices they believe exist in the community to work toward creating an inclusive, socially sustainable community.
Keywords: collective efficacy; self-efficacy; social sustainability; inclusion; agency; social capital